Supply chain management and advanced planning concepts, models, software and case studies - Stadtler, Hartmut. (Springer, 2005)
Supply Chain Management concerns organizational aspects of integrating legally separated firms as well as coordinating material and information flows within a production-distribution network. Enterprise Resources Planning (ERP) systems being used for transaction handling and order execution in most firms today have been supplemented by Advanced Planning Systems (APS) for coordinating flows, exploiting bottlenecks and keeping due dates. This book provides insights regarding the concepts underlying APS. Special emphasis is given to modelling supply chains and implementing APS in industry successfully. Understanding is enhanced through the use of case studies as well as an introduction to the solution algorithms used. For the third edition the content of the book has been updated thoroughly taking into account latest APS software developments, research results and experiences with APS implementation projects. Two new case studies have been added resulting in a total of six case studies now covering a wide range of industrial sectors and ideas to implement APS successfully. Finally, a new chapter on "Purchasing & Material Requirements Planning" complements the description of APS. Basics of Supply Chain Management -- Supply Chain Management — An Overview -- Supply Chain Analysis -- Types of Supply Chains -- Advanced Planning -- Concepts of Advanced Planning Systems -- Structure of Advanced Planning Systems -- Strategic Network Planning -- Demand Planning -- Master Planning -- Demand Fulfilment and ATP -- Production Planning and Scheduling -- Purchasing and Material Requirements Planning -- Distribution and Transport Planning -- Coordination and Integration -- Collaborative Planning -- Implementing Advanced Planning Systems -- The Definition of a Supply Chain Project -- The Selection Process -- The Implementation Process -- Actual APS and Case Studies -- Architecture of Selected APS -- SCM in a Pharmaceutical Company -- Food and Beverages -- Computer Assembly -- Demand Planning of Styrene Plastics -- Semiconductor Manufacturing -- Scheduling of Synthetic Granulate -- Conclusions and Outlook -- Conclusions and Outlook -- Supplement -- Forecast Methods -- Linear and Mixed Integer Programming -- Genetic Algorithms -- Constraint Programming.